The Unstable Distal Radius Fracture—How Do We Define It? A Systematic Review - Walenkamp, Monique M. J.; Vos, Lara M.; Strackee, Simon D.; Goslings, J. Carel; Schep, Niels W. L. (Journal of Wrist Surgery, 2015)
Background Unstable distal radius fractures are a popular research subject. However, to appreciate the findings of studies that enrolled patients with unstable distal radius fractures, it should be clear how the authors defined an unstable distal radius fracture.Questions In what percentage of studies involving patients with unstable distal radius fractures did the authors define unstable distal radius fracture? What are the most common descriptions of an unstable distal radius fracture? And is there one preferred evidence-based definition for future authors?Methods A systematic search of literature was performed to identify any type of study with the term unstable distal radius fracture. We assessed whether a definition was provided and determined the level of evidence for the most common definitions.Results The search yielded 2,489 citations, of which 479 were included. In 149 studies, it was explicitly stated that patients with unstable distal radius fractures were enrolled. In 54% (81/149) of these studies, the authors defined an unstable distal radius fracture. Overall, we found 143 different definitions. The seven most common definitions were: displacement following adequate reduction; Lafontaine's definition; irreducibility; an AO type C2 fracture; a volarly displaced fracture; Poigenfürst's criteria; and Cooney's criteria. Only Lafontaine's definition originated from a clinical study (level IIIb).Conclusion In only half of the studies involving patients with an unstable distal radius fracture did the authors defined what they considered an unstable distal radius fracture. None of the definitions stood out as the preferred choice. A general consensus definition could help to standardize future research.
Keywords: unstable distal radius fracture; instability; generalizability; systematic review; definition